Edukasi Penggunaan Media Sosial Kepada Masyarakat Desa Cigadog Garut - Nurhadi, Zikri Fachrul Nurhadi; Apriliyan, Riyan; Putra, Hagis Erya (Jurnal Media Pengabdian Komunikasi, 2023)
Abstract Social media is media on the internet that allows users to present themselves as a medium for interacting socially in cyberspace. Communicate virtually with other users forming social bands. In social media, three forms are formed which refer to the meaning of being social, namely cognition, communication and collaboration. It cannot be denied that social media has become a new way to communicate today. Along with its development, social media also influences social change in society. Changes in social relations or as changes to the balance of social relations. Positive social changes such as the ease of obtaining and conveying information have social and economic benefits. Meanwhile, social changes tend to be negative, such as the emergence of religious groups, tribes, and certain behavioral patterns that deviate from existing norms. In this service, the author uses lecture and discussion methods. The results of this service have a positive impact on the use of social media which has actually had an influence on social change in society for the better, but the negative impact tends to bring about social change in society which eliminates the values or norms of Indonesian society. With the presence of social media as a new technology, of course the way humans live will also experience changes. Keywords: Impact; education; social media.  AbstrakMedia sosial yaitu media pada internet yang memungkinkan penggunanya untuk dapat mempresentasikan dirinya seklaigus sebagai media untuk berinteraksi secara social di dunia maya. Berkomunikasi secara virtual dengan pengguna lain membentuk social banding. Dalam media social, terbentuk tiga wujud yang merujuk untuk makna bersosial, yaitu, cognition, communicate dan cooperation. Tidak dapat dipungkiri bahwa media social sudah sebagai cara baru untuk berkomunikasi saat ini. Seiring dengan perkembangannya, media social juga berpengaruh terhadap perubahan sosial masyrakat. Perubahan-perubahan dalam hubungan social atau sebagai perubahan terhadap keseimbangan hubungan social. Perubahan social positif seperti kemudahan memperoleh dan menyampaikan informasi memperoleh keuntungan secara social dan ekonomi. Sedangkan perubahan social yang cenderung negtaif seperti munculnya kelompok-kelompok agama, suku, dan pola perilaku tertentu yang menyimpang dari norma-norma yang ada. Dalam pengabdian ini, penulis menggunakan metode ceramah dan diskusi. Hasil pengabdian ini berdampak positif penggunaan media sosial secara nyata telah membawa pengaruh terhadap perubahan sosial masyarakat kearah yang lebih baik tetapi dampak negatif cenderung membawa perubahan sosial masyarakat yang menghilangkan nilai – nilai atau norma di masyarakat Indonesia. Dengan hadirnya media sosial sebagai teknologi baru, tentu saja cara hidup manusia juga akan mengalami perubahan.Kata-kata kunci: Dampak; edukasi; media sosial.